2013
DOI: 10.1103/physrevb.88.024118
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence of orbital order inα-B12andγ-B28

Abstract: The electron density of the α form of boron has been obtained by multipole refinement against high-resolution, single-crystal x-ray diffraction data measured on a high-quality single crystal at a temperature of 100 K. Topological properties of this density have been used to show that all chemical bonds between B 12 clusters in α-B 12 are formed due to one orbital on each boron atom that is oriented perpendicular to the surface of the cluster. It is shown that the same orbital order on B 12 clusters persists in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
34
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 36 publications
14
34
0
Order By: Relevance
“…These values are consistent with a recent study by S. Mondal et al [7]. B p and B e indicate the polar and equatorial atom, respectively.…”
Section: X-ray Charge Density Of α α α α-B 12supporting
confidence: 93%
See 3 more Smart Citations
“…These values are consistent with a recent study by S. Mondal et al [7]. B p and B e indicate the polar and equatorial atom, respectively.…”
Section: X-ray Charge Density Of α α α α-B 12supporting
confidence: 93%
“…The distances distributed from 1.6676(4) to 2.0105(4) Å, which are very similar to the results of the reference studies [6,7].…”
Section: X-ray Charge Density Of α α α α-B 12supporting
confidence: 84%
See 2 more Smart Citations
“…In the second study of α‐B 12 , the bonding pattern within the icosahedra was shown to be very similar in the two polymorphs . Furthermore, the inter‐icosahedral bonding was shown to consist of both strong 2c2e bonds (in fact the strongest bonds in the material) and weaker 3c2e bonds.…”
Section: Materials Classesmentioning
confidence: 93%